Does An ERAS Protocol Reduce Postoperative Opiate Prescribing in Plastic Surgery?. (March 2022) - Faulkner, Heather R.; Coopey, Suzanne B.; Sisodia, Rachel; Kelly, Bridget N.; Maurer, Lydia R.; Ellis, Dan
Summary: Background: Enhanced recovery after surgery (ERAS) protocols are effective at reducing inpatient opiate use. There is a paucity of studies on the effects of an ERAS protocol on outpatient opiate prescriptions. The aim of this study was to determine whether an ERAS protocol for plastic and reconstructive surgery would reduce opiate use in the outpatient postoperative setting. Methods: A statewide (Massachusetts, USA) controlled substance prescription monitoring database was retrospectively reviewed to assess the prescribing patterns of a single academic plastic surgeon performing common plastic surgical outpatient operations. The time period prior to implementation of the ERAS protocol was then compared with the time period following protocol implementation. An additional three months of post-implementation data were then compared with those of each of the previous time periods to investigate whether the results were sustained. Results: A comparison of opiate prescriptions in pre-ERAS, immediate post-ERAS procedures, and follow-up ERAS implementation procedures revealed a statistically significant decrease in opiate prescriptions after ERAS protocol implementation. This decrease in the quantity of opiates prescribed was sustained over time . Conclusions: ERAS protocols are effective at reducing outpatient opiate prescriptions after a variety of plastic surgery operations. Appropriate patient and physician education is paramount for success.